2010
DOI: 10.5688/aj740578
|View full text |Cite
|
Sign up to set email alerts
|

First-year Pharmacy Students' Self-Assessment of Communication Skills and the Impact of Video Review

Abstract: Objectives. To determine the ability of first-year students to self-assess communication skills and measure the impact of video review on students' self-assessment. Design. Students participated in a digital video-recorded, counseling-simulation exercise and completed self-assessment before and after viewing their video. A faculty member evaluated the students using the same counseling assessment tool. Assessment. Correlation between the students' self-assessment scores and the faculty member's scores were poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 26 publications
(64 reference statements)
4
46
0
3
Order By: Relevance
“…1,13 Quality of self-assessment may be influenced by a student's academic ability, as students who are in the lowest GPA quartiles tend to overestimate their skills while those in higher quartiles are more likely to underestimate them. 1,14 Possible explanations for the small differences between faculty and student grading in the current study may be that most of the participating students had a high GPA (3.4 of possible 4.0), and 4 of the 31 faculty members gave all their students during the study year a 4.0, which may have increased the mean faculty GPA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1,13 Quality of self-assessment may be influenced by a student's academic ability, as students who are in the lowest GPA quartiles tend to overestimate their skills while those in higher quartiles are more likely to underestimate them. 1,14 Possible explanations for the small differences between faculty and student grading in the current study may be that most of the participating students had a high GPA (3.4 of possible 4.0), and 4 of the 31 faculty members gave all their students during the study year a 4.0, which may have increased the mean faculty GPA.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies indicated that using video recordings as an assessment tool improved students' self-confidence, interviewing, and self-assessment skills. 13,14,16 As in our study, using a detailed rubric-based evaluation form that includes assessment of professional behavior, performance on various skills, and knowledge also may facilitate the process. 4 Limitations of the study include that it was confined to only 1 academic year and there was a low response to the alumni survey.…”
Section: Discussionmentioning
confidence: 99%
“…The value of this intervention is decreased if the student is sent into the practice experience with no former communication skills training. 67,72 Although practice experiences in a pharmacy setting seem to be accepted as an effective way to improve interpersonal communication skills as well as some forms of written communication skills, in general they are difficult to arrange and draining to available resources such as educated preceptors, and there is a lack of appropriate assessment methods. 72,74 Portfolios are a method used to assess students' skill and knowledge development in pharmacy practice experiences, often including communication skills assessments.…”
Section: Discussionmentioning
confidence: 99%
“…and interpersonal skills, the students' pre-and post-video scores were significantly different (p=0.001 and p<0.0001, respectively) than those prior to video review. Although the correlation to faculty ratings did not improve in this case, activities such as these may provide students the opportunity to practice and utilize the videotape as a tool to assist in the recognition of strengths and weaknesses (Mort & Hansen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of videotape review on pharmacy students' self-assessments of communication skills was recently studied by Mort and Hansen (2010). First-year students in a pharmacy practice course participated in a digitally recorded counseling exercise.…”
Section: Introductionmentioning
confidence: 99%